-3(-4-n)=8(n-6)-5n

Simple and best practice solution for -3(-4-n)=8(n-6)-5n equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-4-n)=8(n-6)-5n equation:



-3(-4-n)=8(n-6)-5n
We move all terms to the left:
-3(-4-n)-(8(n-6)-5n)=0
We add all the numbers together, and all the variables
-3(-1n-4)-(8(n-6)-5n)=0
We multiply parentheses
3n-(8(n-6)-5n)+12=0
We calculate terms in parentheses: -(8(n-6)-5n), so:
8(n-6)-5n
We add all the numbers together, and all the variables
-5n+8(n-6)
We multiply parentheses
-5n+8n-48
We add all the numbers together, and all the variables
3n-48
Back to the equation:
-(3n-48)
We get rid of parentheses
3n-3n+48+12=0
We add all the numbers together, and all the variables
60!=0
There is no solution for this equation

See similar equations:

| 11/4x+9=3 | | 5/8n-9=1 | | 3(3x+3)=-5(5x-5)-3x | | n^2-48=-2n | | (120/8)=(17/x) | | 9x-4=2x+94 | | -83-7x=-15x+5 | | -7-4x=-5x+6 | | -8(x+1)=-5x-35 | | 4x+5=6x-6 | | 2(5x+4)=-5(5x-4) | | 8y=8+6y | | 28-4x=15+9x | | x+7=5x-53 | | 1/2(x+5)-4=1/3=(2x-1) | | -7(2r-1)+3(8-r)=0 | | 5x-8(x+5)=√3-3x | | n÷9=4 | | x=2.62=6.37 | | −48−7n=9n−5(4n+8) | | h+(h+6)+4(h+6)=126 | | 16=8x+1-5 | | -(z+5=-14 | | 8x-10/5=2 | | -18=3(v-4)-6v | | 12k-50=2(2k)+2(3) | | 5x+7x-9=3(4x+8) | | 4x-36=-5x | | -10x-19=-5x+26 | | 2x-8-4x=6x+9x+4 | | 2z+6z-451=2485 | | 30=6x-42 |

Equations solver categories